Local sequence context at KRAS codons modulates DNA repair efficiency: insights from molecular dynamics simulations - Davies, James; Menzies, Georgina E. (Frontiers in Molecular Biosciences, 2025)
IntroductionBenzo[a]pyrene diol-epoxide (BPDE)-induced DNA adducts contribute to the disproportionate mutagenesis of codon 12 in the KRAS gene, driven by preferential DNA damage and impaired repair. Codon susceptibility, however, extends beyond oncogenic hotspots, suggesting that BPDE lesions may serve as biomarkers of individual DNA repair capacity and cancer risk. While the genotoxic effects of tobacco smoke are well characterised, their influence on DNA repair remains underexplored.MethodsHere, we modelled BPDE-adducted KRAS sequences at codons 12 and 14, which have been suggested to exhibit differential repair rates, to assess local helical distortion and its impact on nucleotide excision repair (NER).ResultsWe show that BPDE adduction at codon 12 induces distinct DNA distortion compared to codon 14, appearing closer to the canonical DNA structure and therefore potentially evading DNA repair, resulting in altered Rad4 binding and compromised lesion recognition.DiscussionOur findings link the mutational hotspot at KRAS codon 12 to impaired NER and highlight the critical role of local sequence context in repair efficiency. These results provide new insights into the interplay between sequence-dependent DNA structure and repair, with implications for mutation accumulation and cancer development.